2022
DOI: 10.1186/s13100-022-00283-1
|View full text |Cite
|
Sign up to set email alerts
|

The coevolution between APOBEC3 and retrotransposons in primates

Abstract: Retrotransposons are genetic elements with the ability to replicate in the genome using reverse transcriptase: they have been associated with the development of different biological structures, such as the Central Nervous System (CNS), and their high mutagenic potential has been linked to various diseases, including cancer and neurological disorders. Throughout evolution and over time, Primates and Homo had to cope with infections from viruses and bacteria, and also with endogenous retroelements. Therefore, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 147 publications
0
3
0
Order By: Relevance
“…In addition, evolutionary analyses of APOBEC3 proteins indicate that they have been under strong selective pressure over the last 30 million years. Additionally, polymorphisms have been found that contribute significantly to their antiviral efficacy [ 45 , 46 , 47 ].…”
Section: Apobec Proteins and Their Role In Viral Inhibition And Genom...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, evolutionary analyses of APOBEC3 proteins indicate that they have been under strong selective pressure over the last 30 million years. Additionally, polymorphisms have been found that contribute significantly to their antiviral efficacy [ 45 , 46 , 47 ].…”
Section: Apobec Proteins and Their Role In Viral Inhibition And Genom...mentioning
confidence: 99%
“…Traces of APOBEC mutations have been identified in the genomes of vertebrates, implying that APOBECs were important players in the restriction of retroelements and influenced their evolution [ 15 , 45 , 49 ]. Similar to the editing-independent inhibition of viral replication [ 50 ], the restriction of retrotransposition could also be editing-independent [ 14 , 46 , 49 , 51 , 52 ].…”
Section: Apobec Proteins and Their Role In Viral Inhibition And Genom...mentioning
confidence: 99%
“…And in reference to immune strategies to treat cancer, activation of LINE1 transcription has been shown to be a major mechanism of T cell exhaustion [89]. In response to transposon infection, particularly that of LINE1, primates also underwent a rapid expansion of the APOBEC3 family of cytosine deaminases which degrade transposons by inducing mutations in them [90]. Yet another mechanism of transposon suppression involves a family of zinc finger proteins that bind as transcription factors to methylated CpGs and play a critical role in gene regulation.…”
Section: Emergence Of Transposons Within the Primate Genome Coincides...mentioning
confidence: 99%